A Rural-Urban Comparison of Manufacturing Enterprise Performance in Ethiopia - Rijkers, Bob (2012)
Manufacturing enterprises in rural and urban Ethiopia are compared to examine how location and investment climate characteristics affect performance. Urban firms are larger, more capital intensive and have higher labor productivity than rural firms, yet there is no strong evidence of increasing returns to scale. The hypothesis that firms in rural towns have the same average total factor productivity as urban firms is not rejected; however, firms in remote rural areas are less productive. Rural firms grow less quickly than urban firms. These results can partly be attributed to differences in the quality of infrastructure, access to credit and transportation costs across rural and urban areas. Since rural firms operate in a business environment that is very different from its urban counterpart, lessons derived from urban investment climate surveys cannot immediately be transferred to rural areas.